Pollination Markets and the Coupled Futures of Almonds and Honey Bees: Simulating Impacts of Shifts in Demands and Costs. (31st August 2018) - Lee, Hyunok; Sumner, Daniel A.; Champetier, Antoine
Abstract: Honey bees have garnered much attention in recent years. Concerns about long‐term sustainability of pollinator populations have been coupled with concerns about implications for food supplies. We use a novel formulation of a multiple input, multiple output, two season equilibrium simulation model to explore economic linkages across the markets of buyers and sellers of pollination services and honey. We specify and calibrate in a tractable way the empirical relationships between pollinators and the crops they pollinate, especially almonds. Our model highlights the sequential nature of the pollination season and implication for revenue from pollination and honey production. We demonstrate how shifts in almond supply and demand and the much‐discussed honey bee hive health problems cause price and quantity adjustments in horizontally and vertically related markets and quantify these effects. We show that the economic fortunes of the almond industry, including demand growth, cost concerns, and the potential for new almond varieties that use fewer bees, crucially affect the returns to beekeeping and the number of hives. These drivers of almond economics also have substantial effects on the cost of pollination for crops that are pollinated later.